Diversity Management in the Public Sector for Sustainable, Inclusive Organizations: Ideals and Practices in Northwest Florida. (3rd September 2022) - Atkinson, Christopher L.; Alibašić, Haris; Oduro Nyarko, Emmanuel
Abstract: Diversity management in the workplace is essential for ensuring a high quality, representative public service and strengthening organizations' sustainability. For the public sector to remain effective and productive, the management of today's dynamic workforce requires a perspective that values and welcomes diversity. The promotion of diversity in the public sector helps to ensure sustained competitiveness and success. This study explores managing diversity in the public sector and how public organizations' human resources have engaged with diversity. Semi-structured interviews with 37 officials working in Human Resource departments in the public sector, primarily in Northwest Florida, USA, were conducted by student researchers. A grounded theory approach to understanding the interviews was conducted, using two-cycle coding. Interviewees indicated that diversity recruitment and diversity education ensured high inclusion levels concerning race/ethnicity, age, and gender in the public sector, echoing the literature on the topic; this showed the importance of maintaining such emphases. Analysis of the interviews indicated continuing challenges with attaining the ideals of diversity. By providing attention to workforce diversity and insights into diversity management in the public sector organizations in the United States deserving of additional attention, this study contributes to understanding managing diversity to attain public sector success.